Trayectoria tecnológica Web y el orden digital en Latinoamérica: reflexiones históricas desde Brasil - Berrío-Zapata, Cristian [UNESP]; Vicentini Jorente, María José [UNESP]; Gonçalves Santana, Ricardo Cesar [UNESP] (Escuela Interamericana de Bibliotecología, 2014)
The emergence of the digital order renewed the Victorian civilizing ideal and strengthened a world order of techno-economic dependence. The new grand narrative is the urgency of digital transformation of societies; a dream pursued without reflection by the populations of the periphery that ended into in a collision between McLuhan's two informational orders: cold and hot societies. Latin America as part of the periphery did not participate in the development of the informatic technologies and its historical legacy made the appropriation of these technologies more difficult. This paper examines the historical circumstances of this process: the development of a discourse around the digital networks, the consequences of this social construction in the region, the fragile efforts of Brazil to create technology, and the entrance of IT networks in the region. The results showed that the status of this kind of research in the region is weak so we alert about its consequences. We concluded that to create an informational order that may serve as a space of self-affirmation, freedom and heterogeneity, it is necessary to have a deep knowledge of the social and historical context that created its basic technologies, but Latin America is indifferent in such regard. Information Science has a central role in the region within this process but it has not developed it yet.

La emergencia del orden digital renovó el ideal civilizador victoriano y afianzó un orden mundial de dependencia tecno económica: el modelo centro-periferia. La nueva gran narrativa global es la urgencia de la transformación digital de todas las sociedades; un sueño perseguido irreflexivamente por los pueblos de la ''periferia'', y convertido en un choque entre sociedades informacionalmente ''frías'' y ''calientes''. Latinoamérica como ''periferia'', no participó del desarrollo de la tecnología informática. Adicionalmente, su legado histórico ha dificultado la apropiación de la misma. Este artículo examina las circunstancias históricas de desarrollo de las redes digitales y sus consecuencias desde la construcción social del discurso, recuperando el desarrollo de estas tecnologías, los tímidos intentos de Brasil en participar de este proceso y la entrada de las redes informáticas en la región. Se encontró que el estado de la investigación en el área es débil, y se alerta sobre las posibles consecuencias de ello. Se concluye que para gestionar un orden informacional que sirva de espacio de autoafirmación, con libertad y heterogeneidad, es preciso tener conocimiento profundo sobre el contexto histórico y social que creó sus tecnologías de base, y Latinoamérica es indiferente en esta materia. La Ciencia de la Información regional tiene un papel central en este proceso pero no lo ha desarrollado aún.
Web technological path and digital order in Latin America: historical reflections from Brazil
Keywords: Web; Internet; Latin America; ICT; History